Vortex-Assisted Surfactant-Enhanced Emulsification Microextraction Combined with High Performance Liquid Chromatography-Fluorescence Detector for Determination of Nitrite in Urine - Ning, Jinyan; Zhao, Jiao; Meng, Lifen; Bi, Li (Asian Journal of Chemistry, 2014)
A vortex-assisted surfactant-enhanced emulsification microextraction (VASEME) combined with high performance liquid chromatography-fluorescence detector (HPLC-FLD) procedure was developed for the determination of trace nitrite in human urine. The method is based on the selective reaction of nitrite with o-phenylenediamine in acid media to form benzotriazole, which exhibited strong fluorescence at 568 nm with excitation at 420 nm in alkaline medium. The fluorescence of system was enhanced by hydroxypropyl-b-cyclodextrin (HP-b-CD) through complexation. The nonionic surfactant Triton X-114 was adopted as emulsifier and n-octanol as the extraction solvent and vortex-mix was applied to assist emulsification in vortex-assisted surfactant-enhanced emulsification microextraction. Under the optimal conditions: the linearity was observed in the range of 4 to 80 ng/mL and the correlation coefficient ( r) was 0.996. The relative standard deviations were below 3.7 % (n = 5). The limit of detection (LOD) based on a signal-to-noise ratio (S/N) of 3 was 0.08 ng/mL and a signal-to-noise ratio (S/N) of 10 the quantification limits (LOQ) was 0.314 ng/mL. Good recoveries (³ 85 %) were obtained when the proposed method was applied to determine nitrite in human urine samples.